The MazEF Toxin-Antitoxin System Alters the β-Lactam Susceptibility of Staphylococcus aureus. - Christopher F Schuster; Lukas Mechler; Nicoletta Nolle; Bernhard Krismer; Marc-Eric Zelder; Friedrich Götz; Ralph Bertram (PLoS ONE, 2015)
Toxin-antitoxin (TA) systems are genetic elements of prokaryotes which encode a stable toxin and an unstable antitoxin that can counteract toxicity. TA systems residing on plasmids are often involved in episomal maintenance whereas those on chromosomes can have multiple functions. The opportunistic pathogen Staphylococcus aureus possesses at least four different families of TA systems but their physiological roles are elusive. The chromosomal mazEF system encodes the RNase toxin MazF and the antitoxin MazE. In the light of ambiguity regarding the cleavage activity, we here verify that MazF specifically targets UACAU sequences in S. aureus in vivo. In a native strain background and under non-stress conditions, cleavage was observed in the absence or presence of mazE. Transcripts of spa (staphylococcal protein A) and rsbW (anti-σB factor) were cut, but translational reporter fusions indicated that protein levels of the encoded products were unaffected. Despite a comparable growth rate as the wild-type, an S. aureus mazEF deletion mutant was more susceptible to β-lactam antibiotics, which suggests that further genes, putatively involved in the antibiotic stress response or cell wall synthesis or turnover, are controlled by this TA system.